INTERCULTURAL COMMUNICATION: HOW PATTANI STUDENTS COMMUNICATE TO KEMBANGARUM RESIDENTS - Muhammad Nuryanto (Universitas Samudra, 2021)
The research aimed to examine (1) the anxiety experienced by Pattani Students when they first mingled with Kembangarum residents, (2) the anxiety management used by Pattani Students, (3) the model of intercultural communication between Pattani students and Kembangarum residents. The type of the research used in this study is a case study. While the approach was qualitative approach. Data collection techniques used were in-depth interviews and participatory observation. The subject of the study is Pattani students and Kembangarum residents. The findings showed there was a cultural shock experienced by Pattani students when they first lived in Kembangarum. The cultural shock resulted in anxiety and uncertainty when they communicate with the locals. To overcome this anxiety, Pattani students used Gudykunst’s three anxiety management, those are the self-concept, motivation and, reaction to the locals. The communication model used by Pattani students was intercultural approaches by prioritizing dialectics and interpretation of community behavior.